Exercise-induced bronchoconstriction in athletes - should we screen? - Hull, J. H. K.; Ansley, L.; Garrod, R.; Dickinson, J. W. (Medicine & Science in Sports & Exercise, 2007)
The fact that exercise-induced bronchoconstriction (EIB) may be both over- and underdiagnosed in athletes has led to calls for widespread screening for the condition. This article assesses such a strategy by employing the standard framework used when evaluating any screening policy. This approach highlights a number of concerns and allows recommendations to help optimize the success of such a strategy if it were to be implemented.